Avaliação da atividade antitumoral do óleo essencial da Mentha x villosa (Lamiceae) - Amaral, Ricardo Guimarães (2014)
Cancer is the given name for a group of more than 100 diseases account for 13% of deaths worldwide and 15.1% in Brazil, with estimates of increased mortality. These data show the deficiency of more effective anticancer agents, leading to increased life expectancy or cure. In this context, nature is an alternative to the problem, for harboring a huge biodiversity and Brazil stands out for having the highest diversity of plant species in the world, but little explored as their biological characteristics. The genus Mentha has its very widespread species in the country, with many evidenced therapeutic activities, among them the potential anticancer action of essential oil (EO) demonstrated in two species (Mentha piperita e Mentha spicata). However, this study aimed to evaluate the antitumor activity of the essential oil of Mentha x villosa Hudson (OEMV) in vitro and in vivo, and its toxicity in vivo. For this, the EO was extracted from the leaves of Mentha x villosa, 12 of its constituents have been identified and their main constituent, the monoterpene rotundifolone was isolated. The in vitro cytotoxicity of OEMV rotundifolone and 3 were evaluated against tumor cell lines: ovarian adenocarcinoma (OVACAR-8), colon carcinoma (HCT-116) and glioblastoma (SF295) by the MTT assay. The OEMV showed cytotoxic activity in all cell lines tested, with IC50 ranging from 0.57 to 1.02 ìg/mL. However, rotundifolone did not show cytotoxicity at the tested concentrations, suggesting that the activity of the oil is not mediated by its major constituent. Considering this result, we evaluated the antitumor activity of OEMV in vivo using mice transplanted with sarcoma 180. In this study, it was showed antitumor activity in OEMV treatments performed by intraperitoneal (32.02 and 42.81% with 50 and 100 mg/kg/day, respectively) and orally (34.27 and 43.22% with 100 and 200 mg/kg/day, respectively), probably due to synergy among its constituents. No change was observed in the toxicological parameters evaluated in animals treated with OEMV: variation in body mass, organ weights (liver, spleen and kidney), blood biochemical parameters (AST, ALT, urea and creatinine) and ulcerative lesion index (this later only in the groups treated orally). Since the results demonstrated that OEMV has antitumor activity with low toxicity, it was proposed to evaluate the benefit of the association between OEMV (50 and 100 mg/kg/day) and 5-fluorouracil (5-FU, 10 mg/kg/day) reference known antineoplasic and toxicity. The association promoted tumor growth inhibition of 50.3% and 65.2% at doses of 50 and 100 mg/kg/day, respectively. The highest dose of OEMV in combination showed the same statistical difference that the level of inhibition of 5-FU at the highest dose (25 mg/kg/day). The toxicological parameters, variation of body mass and biochemical parameters (AST and ALT) showed alterations similar as the positive control. The organ weight alterations did not occur, a result that demonstrates an evident benefit of the combination compared to the group treated with 5-FU alone. The last toxicological endpoints evaluated were hematological parameters where both groups showed changes associated with differential count (lymphocytosis and neutropenia) and reduction in total leukocytes; positive factor in this result is that the reduction was not as intense as the one displayed by the control 5-FU furthermore possibly resulting in a decreased susceptibility to infection. The association promoted tumor growth inhibition 50.3% and 65.2% at doses of 50 and 100 mg/kg/day, respectively. The highest dose of OEMV in combination showed the same statistical difference that the level of inhibition of 5-FU dose (25 mg/kg/day) the toxicological parameters, variation of body mass and biochemical analysis (AST and ALT) showed alterations similar to the positive control.